2010
DOI: 10.1002/cssc.201000271
|View full text |Cite
|
Sign up to set email alerts
|

Green and Sustainable Chemical Synthesis Using Flow Microreactors

Abstract: Several features that allow flow microreactors contribute to green and sustainable chemical synthesis are presented: (1) For extremely fast reactions, kinetics often cannot be used because of the lack of homogeneity of the reaction environment when they are conducted in batch macroreactors. Better controllability, by virtue of fast mixing based on short diffusion paths in microreactors, however, leads to a higher selectivity of the products, based on kinetics considerations. Therefore, less waste is produced. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
168
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 409 publications
(171 citation statements)
references
References 152 publications
0
168
0
2
Order By: Relevance
“…The excellent thermal conductivity and high surface-to-volume ratio of microreactors are especially useful in studying extremely fast and exothermic reactions, and for the control of highly reactive, short-lived reactive intermediates. 30 Yoshida et al 31 have demonstrated such control by performing the enantioselective carbolithiations of conjugated enynes 2 with a chiral organolithium species 1, followed by the addition of the unstable intermediates 3 to various electrophiles, obtaining enantioenriched chiral allenes 4. Their microfluidic system consisted of three T-shaped micromixers (M1, M2, and M3) and three microtube reactors (R1, R2, and R3) ( Figure 8).…”
Section: Heat Transfermentioning
confidence: 98%
See 1 more Smart Citation
“…The excellent thermal conductivity and high surface-to-volume ratio of microreactors are especially useful in studying extremely fast and exothermic reactions, and for the control of highly reactive, short-lived reactive intermediates. 30 Yoshida et al 31 have demonstrated such control by performing the enantioselective carbolithiations of conjugated enynes 2 with a chiral organolithium species 1, followed by the addition of the unstable intermediates 3 to various electrophiles, obtaining enantioenriched chiral allenes 4. Their microfluidic system consisted of three T-shaped micromixers (M1, M2, and M3) and three microtube reactors (R1, R2, and R3) ( Figure 8).…”
Section: Heat Transfermentioning
confidence: 98%
“…30 One such example is the Li-Br exchange reaction of p-dibromobenzene with n-BuLi. By carefully controlling residence times of each step using micromixers, sequential addition of lithiation and electrophiles was achieved ( Figure 33).…”
Section: Multistep Synthesismentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] (1) Precise control of short reaction times (<1 sec) can be achieved.…”
Section: Advantages Of Micro-flow Synthesis Over Conventional Batch Smentioning
confidence: 99%
“…Such miniaturized platforms are also very attractive as more sustainable and safe research and development platforms especially when working with hazardous or highly reactive compounds. Due to the minimal resource consumption and enhanced reaction rates of diffusionlimited processes [30][31][32][33], such microdevices are promising tools for fast optimization and investigation of chemical syntheses [34][35][36][37][38], such as catalyst screening.…”
Section: Introductionmentioning
confidence: 99%